ҚАРАҚАЛПАҚ ТИЛИ АРҚА ДИАЛЕКТИ СӨЙЛЕСИМЛЕРИНДЕГИ ФОНЕТИКАЛЫҚ ҚУБЫЛЫСЛАР - Қайпназарова, М.К. (ILIM hám JÁMIYET, 2016)
The article deals with the analysis of phonetic peculiarities of the northern dialects of the Karakalpak language and phonetic qualities of the vowels and consonants in comparison with the literary language.